Anteroinferior Hip Instability in Flexion During Dynamic Arthroscopic Examination Is Associated With Abnormal Anterior Acetabular Horn. Issue 12 (18th December 2020) - Hatem, Munif A.; Helal, Asadullah; Khoury, Anthony N.; Martin, Hal David
Background: The stabilization of the femoral head is provided by the distal acetabulum when the hip is in a flexed position. However, the osseous parameters for the diagnosis of hip instability in flexion are not defined. Purpose/Hypothesis: To determine whether the osseous parameters of the distal acetabulum are different in hips demonstrating anteroinferior subluxation in flexion under dynamic arthroscopic examination, compared with individuals without hip symptoms. The hypothesis was that the morphometric parameters of the anterior acetabular horn are distinct in hips with anteroinferior instability compared with asymptomatic hips. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 30 hips with anteroinferior instability in flexion under dynamic arthroscopic examination were identified. A control group of 60 hips (30 patients), matched by age and sex, was formed from individuals who had undergone pelvis magnetic resonance imaging (MRI) for nonorthopaedic reasons. Unstable and control hips were compared according to the following parameters assessed on axial MRI scans of the pelvis: anterior sector angle (ASA), anterior horn angle (AHA), posterior sector angle (PSA), posterior horn angle (PHA), acetabular version, lateral center-edge angle, acetabular inclination (Tönnis angle), and femoral head diameter. Results: The coverage of the femoral head by the anterior acetabular horn was decreased in unstable hips compared with the control group (mean ASA, 54.8° vs 61°, respectively; P < .001). Unstable hips also had a steeper anterior acetabular horn, with an increased mean AHA compared with controls (52.5° vs 46.8°, respectively; P < .001). An ASA <58° had a sensitivity of 0.8, a specificity of 0.68, a negative predictive value of 0.87, and a positive predictive value of 0.56 for anteroinferior hip instability. An AHA >50° had a sensitivity of 0.77, a specificity of 0.72, a negative predictive value of 0.86, and a positive predictive value of 0.57 for anteroinferior hip instability. There was no statistically significant difference in the mean PSA, PHA, acetabular version, lateral center-edge angle, acetabular inclination, or femoral head diameter between unstable hips and controls. Conclusion: Abnormal morphology of the anterior acetabular horn is associated with anteroinferior instability in hip flexion. The ASA and AHA can aid in the diagnosis of hip instability.